2023
DOI: 10.1111/jav.03080
|View full text |Cite
|
Sign up to set email alerts
|

Migration strategies, performance and annual activity budget in a short‐distance migrant, the common starlingSturnus vulgaris

Abstract: Migratory birds typically separate energetically demanding parts of the annual cycle like breeding, moult and migration with some species engaging in so‐called moult‐migration. Moult‐migration is known to occur in starlings from the northern breeding populations, however, little is known about the dynamics of this phenomenon and the costs and benefits for the involved individuals. Here, using state‐of‐the art multi‐sensor geolocators we gathered information about the annual cycles of 10 starlings from two bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, our data debunk the possibility that juveniles copied the distances and directions of conspecifics encountered in the social environment of the translocation sites. These results may be partly explained by recent tracking data showing that for actual migration flights, starlings resorted to nocturnality, and may thereby be more lonesome travellers than previously thought [ 45 ]. Although nocturnality does not necessarily exclude social behaviour, we suggest that this is unlikely since the majority of nocturnally migrating birds travel solo [ 46 ], and to the best of our knowledge, starlings do not produce nocturnal flight calls like, for instance, American wood warblers ( Parulidae ) [ 47 ] and European thrushes ( Turdidae ) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our data debunk the possibility that juveniles copied the distances and directions of conspecifics encountered in the social environment of the translocation sites. These results may be partly explained by recent tracking data showing that for actual migration flights, starlings resorted to nocturnality, and may thereby be more lonesome travellers than previously thought [ 45 ]. Although nocturnality does not necessarily exclude social behaviour, we suggest that this is unlikely since the majority of nocturnally migrating birds travel solo [ 46 ], and to the best of our knowledge, starlings do not produce nocturnal flight calls like, for instance, American wood warblers ( Parulidae ) [ 47 ] and European thrushes ( Turdidae ) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the circadian pattern of migratory activity might re ect actual behaviour in the wild (Schmaljohann et al 2015;Ilieva et al 2023), the observed dynamics of circadian activity suggest that, in the wild, male reed buntings start their migration shortly before sunrise and continue migratory ight some hours during daytime, while females migrate mainly during the second half of the night and cease migration around sunrise. The possibility of continuing the nocturnal migratory ight into the daytime was recently reported in another short-distance migrant, European starling (Sturnus vulgaris), which had been previously assumed to migrate primarily during the day (Vīgants et al 2023). In captive conditions, a similar explanation was recently proposed for circadian activity dynamics in Sedge warblers (Acrocephalus schoenobaenus) in autumn (Ilieva et al 2023).…”
Section: Sex-speci C Migration Speed (Hypothesis 3: Males Travelmentioning
confidence: 93%
“…Juvenile Reed warblers displayed nocturnal flights in the wild well in advance of migration, presumably to form memory for navigation, and corresponding nocturnal restlessness in captivity (Mukhin et al 2005 ). In late summer birds may undertake post-breeding movements, for example for dispersal or to reach moulting locations (Pillar et al 2015 ; Vīgants et al 2023 ).…”
Section: Avian Migrationmentioning
confidence: 99%